Protective coatings based on high-strength concrete - ANOPKO, Dmitriy; BONDARENKO, Olga (Ways to Improve Construction Efficiency, 2025)
As the strength of concrete increases, its fragility also increases, and its plastic deformation properties decrease under short-term and long-term loading, which leads to almost instantaneous destruction of concrete when it reaches its limit state. A solution to this problem can be considered dispersed reinforcement of concrete with fiber, which allows to significantly increase its specific strength, especially in tension and bending, crack resistance, resistance to shock and vibration effects, resistance to abrasion, etc. Dispersed reinforced concretes or fiber concretes include a group of composite materials that include short segments of various fibers (fibers) in a cement matrix. Different types of fibers made of steel, glass, synthetic materials, asbestos, carbon, etc. can serve as fibers. The most common fiber concretes based on Portland cement, reinforced with steel fiber - steel fiber concretes. The surface of the fibers can be profiled, etched and, as an exception, smooth. The amount of fibers introduced into the concrete in most cases ranges from 0.5 to 2% by volume. According to their strength properties, products made using fine-grained fiber concrete (lined pipes, bends, tees, crosses, gutters) withstand loads significantly exceeding 5 MPa and therefore can be widely used to protect equipment from abrasive wear, the effects of aggressive environments and high temperatures, which is confirmed by many years of experience in operating such products in various industries, ensuring an increase in the service life of equipment by 2...6 times. Testing of prototypes of lined pipes showed that their reliability and durability in pressure and gravity pipeline systems increases by 5...10 times compared to electric-welded steel pipes and by 2...3 times compared to high-alloy and bimetallic pipes.